2010
DOI: 10.1148/radiol.09090039
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized3He MR for Sensitive Imaging of Ventilation Function and Treatment Efficiency in Young Cystic Fibrosis Patients with Normal Lung Function

Abstract: Although spirometric results indicate normal lung function, the mean VDI in patients (5.1) found in this study is well above the VDI in healthy subjects (1.6) reported in the literature. A single CPT session induces disparate changes in the distribution and extent of ventilation defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 24 publications
3
80
1
1
Order By: Relevance
“…Bannier et al used HP 3 He MRI in 10 CF patients and found an increase in ventilated area, or a decrease in number of ventilation defects, in patients following chest physical therapy (29). In the present study, we found sensitivity to treatment effects in terms of an increase in functional ventilation measured by HP 3 He MRI following treatment in one of three subjects scanned (the 17-yearold), but not in the other two.…”
Section: Discussionsupporting
confidence: 47%
“…Bannier et al used HP 3 He MRI in 10 CF patients and found an increase in ventilated area, or a decrease in number of ventilation defects, in patients following chest physical therapy (29). In the present study, we found sensitivity to treatment effects in terms of an increase in functional ventilation measured by HP 3 He MRI following treatment in one of three subjects scanned (the 17-yearold), but not in the other two.…”
Section: Discussionsupporting
confidence: 47%
“…Following this, hyperpolarized helium-3 MRI (HP 3 He MRI) has been examined in multiple settings and has shown high sensitivity for the detection of ventilation impairments [34][35][36][37][38][39][40][41][42][43][44]. This typically requires production of hyperpolarized gas on site which is then mixed with nitrogen and administered to patients with a one litre Tedlar Bag.…”
Section: Hyperpolarized Helium-3 Mrimentioning
confidence: 99%
“…The effectiveness of an eleven day intervention with intravenous tobramycin, beta-lactam antibiotic, inhalation of 2.5 mg of recombinant human DNase administrated daily, inhalation of 4 mL of 7% hypertonic saline and chest physiotherapy twice a day was monitored by HP 3 He MRI and showed a 25% increase in VV in treated patients [39]. Improvement in VV was observed despite no changes in FEV 1 [40,41] indicating that HP 3 He MRI may provide greater sensitivity in detecting changes. Unfortunately, there were no noticeable effects of a single bout of chest physical therapy (CPT), however one CPT session may not have been sufficient to visualise effects as effective physiotherapy is an ongoing process and not a single event [41,42].…”
Section: Hyperpolarized Helium-3 Mrimentioning
confidence: 99%
“…However, in one recent study assessing lung function using both spirometry and LCI in ex-preterm children aged 11 years, spirometry was more discriminative than LCI in detecting pulmonary function abnormalities (Lum et al, 2011). Recently, hyperpolarised gas MRI has demonstrated regional ventilation abnormalities in young cystic fibrosis patients with normal lung function (Bannier et al, 2010) and is known to be particularly sensitive to early changes in emphysema (Yablonskiy et al, 2009). Perhaps, the non-invasive longitudinal assessment of lung growth with the use of labeled carbon monoxide (Rosenthal & Bush, 1998;Rosenthal & Bush, 1999) and hyperpolarized gases in magnetic resonance may provide further answers with regard to lung growth and ventilation abnormalities (Eberle et al, 2001).…”
Section: Summary and Implicationsmentioning
confidence: 99%